Comparison between Myocardial Ischemia Evaluation by Fractional Flow Reserve and Myocardial Perfusion Scintigraphy - Issa,Aurora Felice Castro (2018)
Abstract Background: Moderate coronary artery lesions can be, or not, responsible for myocardial ischemia. The functional analysis of these lesions can be performed by invasive and noninvasive methods. Objective: To compare the functional analysis of moderate coronary lesions by fractional flow reserve and myocardial perfusion scintigraphy. Methods: 47 patients with stable coronary artery disease and at least one moderate coronary artery obstruction were prospectively studied. They were submitted to fractional flow reserve and myocardial perfusion scintigraphy with a median interval of 24.5 days between January 2013 and December 2015. There was no change in clinical status or revascularization procedure between the exams. The population variables were described as medians and interquartile range. Fractional flow reserve was performed in one left main coronary artery; 37 left descending coronary arteries; 12 circumflex arteries and 4 right coronary arteries. Fractional flow reserve < 0.8 was considered positive. The comparative analysis between the results of the tests was performed by two-tailed Fisher’s test and a p-value ≤ 0.05 was considered significant. Results: Fractional flow reserve < 0.8 was found in the left main coronary artery (100%); 13 in the left descending coronary artery (35.14%); 6 in circumflex artery (50%) and 2 in the right coronary artery (50%). Among the patients with positive fractional flow reserve, 83% had myocardial ischemia demonstrated by the myocardial perfusion scintigraphy (p = 0.058). When analyzing specifically the left descending coronary artery, 83% of the patients with negative fractional flow reserve showed no ischemia at the myocardial perfusion scintigraphy, but 69% of the patients with positive fractional flow reserve showed no ischemia at the myocardial perfusion scintigraphy (p = 0.413). Conclusion: Disagreements can occur between the results of the functional analysis of moderate coronary lesions by invasive and noninvasive tests.